Impacto en el consumidor en la liberación del precio de la gasolina en Colombia (2020)
This work seeks to analyze the impact that a liberation of the price of gasoline would have in Colombia on the final consumer of this product, bearing in mind that the final consumer is not only the person who directly consumes this fuel, but involves every person who consumes the country's family basket, that is, every Colombian. The impact that liberating the price of gasoline would have will depend on the international price of Brent, and an approximation will be given in economic figures of what the increase or decrease in a Colombian's monthly expenses would be if the policy of liberating the price of gasoline existed in the country, and depending on whether the price of Brent is rising or falling.